Synthesis, DFT Calculations, DNA Interaction, and Antimicrobial Studies of Some Mixed Ligand Complexes of Oxalic Acid and Schiff Base Trimethoprim with Various Metal Ions - Eid Abdalrazaq; Abdel Aziz Qasem Jbarah; Taghreed Hashim Al-Noor; Gassan Thabit Shinain; Mohammed Mahdi Jawad (Indonesian Journal of Chemistry, 2022)
Mixed ligand metal complexes are synthesized from oxalic acid with Schiff base, and the Schiff base was obtained from trimethoprim and acetylacetone. The synthesized complexes were of the type [M(L1)(L2)], where the metal, M, is Ni(II), Cu(II), Cr(III), and Zn(II), L1 corresponds to the trimethoprim ((Z)-4-((4-amino-5-(3,4,5-trimethoxybenzyl)pyrimidine-2-yl)imino)pentane-2-one) as the first ligand and L2 represent the oxalate anion ( ) as a second ligand. Characterization of the prepared compounds was performed by elemental analysis, molar conductivity, magnetic measurements, 1H-NMR, 13C-NMR, FT-IR, and Ultraviolet-visible (UV-Vis) spectral studies. The recorded infrared data is reinforced with density functional theory (DFT) calculations. Also, the recorded and calculated IR spectra of the complexes suggested that the coordination of Schiff base is a bidentate ligand with Cu and Ni complexes and a tridentate ligand with Co, Cr, and Zn complexes. The electronic structures of the complexes were investigated by DFT calculations, showing several degrees of HOMO-LUMO energy gaps between complexes. The complexes were studied for their DNA interaction activities. The synthesized ligand and its metal complexes were evaluated for antimicrobial properties against bacterial strains of Bacillus subtilis (G+), Enterobacter cloacae (G-), and Staphylococcus aureus (G+). These complexes considered in this study showed good antimicrobial activity.